Herbal Medicine "Shulifenxiao" Formula for Nephrotic Syndrome of Refractory Idiopathic Membranous Nephropathy - Hailan Cui; Frank Qiang Fu; Frank Qiang Fu; Baoli Liu; Wei Jing Liu; Wei Jing Liu; Yu Ning Liu (Frontiers Media S.A., 2021)
Background: Treatment for adult patients with refractory idiopathic membranous nephropathy (RIMN) by conventional immunosuppressive regimens is not satisfactory. This study aims to evaluate the effectiveness of Chinese herbal medicine, Shulifenxiao formula, as a promising regimen.Methods: A total of 31 RIMN patients resistant to corticosteroid or immunosuppressive agents were retrospectively analyzed. Shulifenxiao treatment lasted a minimum of 12°months in all patients and extended to 24°months in 11 patients. The primary outcomes [the complete remission (CR) and partial remission (PR)] and secondary outcomes (the serum creatinine and estimated glomerular filtration rate (eGFR) levels) were measured at 6, 12, 18, and 24°months.Results: The data provided an average follow-up of 21 ± 9.16°months from baseline. The remission was attained in 25/31 patients (80.7%: CR 29.0% and PR 51.6%) at 12°months and in 10/11 patients (90.9%: CR 54.6% and PR 36.4%) at 24°months, respectively. Proteinuria reduced from 6.02 g/d at baseline to 0.98 g/d at 12°months (p < 0.001) and to 0.27 g/d at 24°months (p = 0.003); serum albumin increased from 28 g/L to 37.2 g/L at 12°months (p < 0.001) and to 41.3 g/L at 24°months (p = 0.003); eGFR improved from 100.25 ml/min/1.73 m2 to 118.39 ml/min/1.73 m2 at 6°months (p < 0.001) and finally to 111.62 ml/min/1.73 m2at 24°months (p = 0.008). Only two patients developed subsequent relapse.Conclusion: Shulifenxiao formula as a clinical cocktail therapy serves as an alternative therapeutic option for steroid and immunosuppressant-resistant RIMN patients, with a favourable safety profile, though further studies are warranted.Clinical Trial registration:http://www.chictr.org.cn, Chinese Clinical Trials Registry [ChiCTR1800019351].